Express Delivery to the Suburbs. The Effect of Transportation in Europe's Heterogeneous Cities - Miquel-Àngel Garcia-López; Ilias Pasidis; Elisabet Viladecans Marsal (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper provides evidence for the causal effect of the highway and railway infrastructure on the suburbanization of population in European cities. We adopt different measures of transportation infrastructure and estimate their joint effects on suburbanization using a two-step panel approach. Our main results suggest that an additional highway ray displaced approximately 4% of the central city population in European cities over a 10-year period, whereas we find no significant effect for the railways on average. However, railways did cause suburbanization those located in Central-North Europe. When employing the full time span covered by our data and accounting for the diversity of European cities, we find a smaller effect of highways on suburbanization during more recent decades and for ”cities with history”. Factors such as historical urban amenities, traffic congestion, urban policies etc. appear to provide reasonable explanations for these differences. The findings of this paper are novel and provide valuable insights for European regional and transport policies.
Keywords: R40; R20; O40; 330; suburbanization; transportation; Europe